The rearing of pomfret (Colossoma macropomum) with fermented feed by using probiotic in recirculation system - Ayusi Rima Inayah; Rusliadi '; Mulyadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The aim of the study was to determine the effect of using fermented feed by probiotic to the growth rate, body weight, body length, survival, feed efficiency and feed conversion rate of pomfret (Colossoma macropomum) in recirculation system. The treatment in this study was the different dose of probiotic for the feed fermentation, and the doses were 9 ml / kg of feed (P1), 12 ml / kg of feed (P2), 15 ml / kg of feed (P3), 18 ml / kg of feed (P4) and control (unfermented feed). Each treatment was repeated 3 times. The particular size of the Pomfret that were used around 5-6 cm were reared for 40 days in the tarpaulin cube tank (50 x 50 x 50) cm³ with 25 fishes/tank of fish stocking density. The fish were fed by addsatiation three times a day. The results showed that the effect of using fermented feed by probiotic significantly affected to absolute weight growth, absolute length growth, specific growth rate, food efficiency, and food conversion ratio but did not significantly affected survival rate. The best treatment was in P4 where the dose of probiotic was 18 ml / kg of feed which contributed 5.92% of specific growth rate, 8.25 grams of absolute weight growth, 2.91 cm of absolute length growth, 98.27% of food efficiency 98.27, as well as the food conversion ratio became 1.01. Meanwhile, the highest survival rate was in P3 (15 ml of probiotic/ kg of feed) which gave the 96 % of survival rate.Keyword: probiotic, Colossoma macropomun, resirculation systems